1993
DOI: 10.2172/10182257
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and health effects review for obscurant graphite flakes. Final report, 1991 July--1993 May

Abstract: Approved for public release; distribution is unlimited. _-'13. ABSTRACT (Maximum 200words) 14. SUBJECT TERMS 15. NUMBER OF PAGES Aquatic Health effects 53 Terrestrial Graphite flakes 16. PmCECODE Dispersion Environmental effects 17. SECURITY CLASSIFICATION i _B.SECURITY CLASSIFICATION 19. SECURITY CLASSIFICATION 20. LIMITATION OF ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The authors conclude that no bioaccumulation of fog oil from fog oil smoke is occurring at Fort McClellan (3D 1996). However, Driver et al (1993) found that the fog oil formulation under evaluation in that study did show some evidence of bioaccumulation. The physical-chemical properties of fog oil would suggest that fog oil constituents have a moderate potential for bioaccumulation, but this has not been verified in field or laboratory studies.…”
Section: Bioaccumulation and Trophic Transfermentioning
confidence: 76%
See 2 more Smart Citations
“…The authors conclude that no bioaccumulation of fog oil from fog oil smoke is occurring at Fort McClellan (3D 1996). However, Driver et al (1993) found that the fog oil formulation under evaluation in that study did show some evidence of bioaccumulation. The physical-chemical properties of fog oil would suggest that fog oil constituents have a moderate potential for bioaccumulation, but this has not been verified in field or laboratory studies.…”
Section: Bioaccumulation and Trophic Transfermentioning
confidence: 76%
“…Graphite flakes are used as an infrared wavelength obscurant, typically as an additive for fog oil smoke. Driver et al (1993) found little risk, chemically and mechanically, to aquatic or terrestrial systems from obscurant graphite flakes. This environmental assessment evaluated the consequences of performing a field test of the XM56 smoke generator at the U.S. Army Yuma Proving Ground, AZ.…”
Section: Graphite Flakesmentioning
confidence: 98%
See 1 more Smart Citation
“…Various authors have presented additional and more specific information regarding military obscurants and other agents, including those containing graphite and powdered brass (Guelta and Checkai 1995;Driver et al 1993a;Wentsel 1986;Wentsel and Guelta 1986;Hancox 1989;Cataldo et al 1990), anthraquinone (Sendelbach 1989), fog oils (Driver et al 1993b;Katz et al 1980), HC smoke (Shinn et al 1987a), CS gas (Keller et al 1986), and phosphorus (Berkowitz et al 1981).…”
Section: Other Resourcesmentioning
confidence: 99%
“…Grose et al (1986), Cataldo et al (1989) and Driver et al (1993a; present a review of health, environmental, and other effects some military smokes. Schaeffer et al (1986;1987) reported some data and information on field and laboratory exposures of vegetation (Tradescantia, Ambrosia) and native rodents (Perognathus, Peromyocus, Neotoma, Dipodomys spp.,) to obscurant smokes.…”
Section: Other Resourcesmentioning
confidence: 99%